Analisis Klaim Pending BPJS Kesehatan di RSUD Pasar Minggu Tahun 2024 - Wirdah, Wirdah; Soewondo, Prastuti; Kartika Dewi, Endah (Publikasi Indonesia, 2025)
Based on the results of the verification of claims at Pasar Minggu Hospital, the number of pending claims at the end of 2024 has increased both in terms of the number of claims and the cost of claims. In hospitals with a JKN service level of > 80%, the occurrence of pending claims can affect the hospital's cash flow. This study aims to analyze data on pending claim cases to be able to map the group of causes of pending cases. The method of writing the article used is a quantitative cross-sectional design, which is an approach based on data collection that can present information in a short time. As a result, the average number of pending cases at Pasar Minggu Hospital is 5.45% of the total number of claim files filed in 2024, while when viewed from the amount of pending claims, it reaches 17.13%. In inpatient services, the percentage of pending claims based on the number of files on average reached 1.02% and 15.48% when viewed from the value of claims. On the other hand, in outpatient services, the average number of claims based on files is higher, which is 4.43% and in terms of claim value, the portion is 1.66%. The cause of pending claims when reviewed from the number of files is the most due to the aspect of administrative completeness, which is 45.07%. Meanwhile, when viewed from the amount of cost or claim value, the group that caused the most pending claims was due to the aspect of coding rules at 44.10%. The factors that cause pending claims at Pasar Minggu Hospital consist of four factors: human (the service team and casemix have varying levels of understanding of coding and medical aspects, money (the budgeting process for updating coding knowledge and skills is not routine), method (the autoclosing system in the outpatient file claim process, in the inpatient claim process, the coding process is carried out at the end of the service), material (PPK updates have not been done regularly, so there are still variations in services), and machines (the coding system in SIMRS is still done with manual input).